2017
DOI: 10.1111/edt.12327
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of oral‐maxillofacial trauma from violence against women and its associated factors

Abstract: The prevalence of oral-maxillofacial trauma was high, and the main associated factors were place of residence and mechanism of aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
46
0
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 33 publications
6
46
0
19
Order By: Relevance
“…Violence continues to be a serious public health problem in different regions of the world due to reflections on health indicators, influence on the daily lives of individuals and the constant presence of victims in health services . According to data from the World Health Organization, 1.4 million people lose their lives annually and many others sustain non‐fatal injuries resulting from episodes of violence .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Violence continues to be a serious public health problem in different regions of the world due to reflections on health indicators, influence on the daily lives of individuals and the constant presence of victims in health services . According to data from the World Health Organization, 1.4 million people lose their lives annually and many others sustain non‐fatal injuries resulting from episodes of violence .…”
Section: Introductionmentioning
confidence: 99%
“…This is a public health problem that has persisted over the years, despite many actions being taken to minimize its consequences . Physical aggressions have been identified as the most common forms of violence, and studies have increasingly reported high rates of oral and maxillofacial injuries among victims . Among anatomical sites, face corresponds to one of the main targets of aggressors, as it represents the locus of singularity and the identity of the human person, has high aesthetic value and plays a significant role during interpersonal interactions .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations